Visualizing the assembly pathway of nucleolar pre-60S ribosomes - Kater, Lukas; Thoms, Matthias; Ismail, Sherif; Ahmed, Yasar Luqman; Bange, Gert; Sinning, Irmgard; Hurt, Ed (Cell, 2017)
Summary Eukaryotic 60S ribosomal subunits are comprised of three rRNAs and ∼50 ribosomal proteins. The initial steps of their formation take place in the nucleolus, but, owing to a lack of structural information, this process is poorly understood. Using cryo-EM, we solved structures of early 60S biogenesis intermediates at 3.3 Å to 4.5 Å resolution, thereby providing insights into their sequential folding and assembly pathway. Besides revealing distinct immature rRNA conformations, we map 25 assembly factors in six different assembly states. Notably, the Nsa1-Rrp1-Rpf1-Mak16 module stabilizes the solvent side of the 60S subunit, and the Erb1-Ytm1-Nop7 complex organizes and connects through Erb1’s meandering N-terminal extension, eight assembly factors, three ribosomal proteins, and three 25S rRNA domains. Our structural snapshots reveal the order of integration and compaction of the six major 60S domains within early nucleolar 60S particles developing stepwise from the solvent side around the exit tunnel to the central protuberance.